2022
DOI: 10.1002/aocs.12623
|View full text |Cite
|
Sign up to set email alerts
|

A review of fatty epoxide ring opening reactions: Chemistry, recent advances, and applications

Abstract: Fatty epoxides are produced from the corresponding alkenes by oxidation in the presence of peracids or other oxidants. The classic method is the Prilezhaev epoxidation in which peracids are generated by in situ oxidation of formic or acetic acids with hydrogen peroxide. Epoxidized vegetable oils and esters are used directly as biobased plasticizers and stabilizers for poly(vinyl chloride) or as important platform chemicals for the oleochemical industry. Nucleophilic attack at the oxirane moiety affords a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 398 publications
0
36
0
Order By: Relevance
“…13 When good nucleophiles like amines are used, as with epoxy-based resins, accelerators are common; co-catalysts are also frequently exploited under acidic conditions, including with fatty acid-derived epoxides. 14 A systematic examination of the reaction of 1 with acrylic acid demonstrated that, by controlling both concentrations of reagents and temperature, catalysts were not required (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…13 When good nucleophiles like amines are used, as with epoxy-based resins, accelerators are common; co-catalysts are also frequently exploited under acidic conditions, including with fatty acid-derived epoxides. 14 A systematic examination of the reaction of 1 with acrylic acid demonstrated that, by controlling both concentrations of reagents and temperature, catalysts were not required (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the previous studies involving ring opening of methyl oleate and fatty acid epoxides utilized the boron trifluoride catalyst. ,,, However, boron trifluoride’s acceptance as an effective catalyst for this reaction continues to wane not only because it is a homogeneous catalyst but also because of its high toxicity. Some heterogeneous catalysts such as saponite clays and Nafion-silica have been reported as being effective for epoxide ring opening of epoxy methyl oleate. , However, their effectiveness with longer-chain fatty esters is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting surfactants gave promising results that could further be exploited in personal and home care products. A comprehensive list of the nucleophiles most commonly used to functionalize fatty derivatives, as well as the chemistry of fatty epoxide ring-opening reactions leading to valuable chemicals was recently reported by Moser and co-workers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9DO is naturally occurring and can be obtained synthetically by selective reduction of 9DA (Bouzidi et al, 2013). Aliphatic polyesters were of interest due to their applications as components in fibers, coatings, adhesives, and resins (Moser et al, 2022; Rybak & Meier, 2008). Lastly, aliphatic polyesters find use in biomedical fields such as surgery and pharmacology because of their biodegradable and nontoxic nature (Turunc & Meier, 2011).…”
Section: Introductionmentioning
confidence: 99%